Nonlinear stability analysis for severe slugging in an air–water two-phase flow. (February 2023) - Azevedo, G.R.; Baliño, J.L.; Andreolli, I.
Abstract: This works presents a numerical study of the types of severe slugging through nonlinear stability analysis. The Landau equation, considered as an asymptotic solution of a two-phase flow model in a pipeline–riser system, is derived. From the Landau equation, the Landau coefficient μ is calculated and, consequently, the saturation amplitudes of the state variables at the limit cycle are determined. Based on the amplitude of the gas superficial velocity at the bottom of the riser, the condition where severe slugging type 3 ( S S 3 ) occurs can be determined. Also, based on the amplitude of the liquid superficial velocity at the top of the riser, the condition of severe slugging with liquid fallback can be determined. The results are presented in stability maps and are compared with experimental data reported in the literature, with a good agreement. Highlights: Nonlinear stability analysis for severe slugging in air–water systems. Severe slugging cycle is predicted by a Laundau Equation. We develop criteria for severe slugging type 3 and liquid fallback. The model is compared with experimental and numerical data. Stability maps showing a comparison with types of severe slugging.